(3WHbGJ GdeMOKjf HCUHgGf hGdhGQOjf YdjgGs - (3CHi eMeO YHO Gddg Hf eMeO Hf LYaQ Hf MHGfs; (3YHO GdQMef Hf CHj HcQ Hf eMeO GHf SGHb GdOjf GdNVjQj GdSjhWj, LdGd GdOjf,J (B911 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hUdi dGdg Ydi eMeO hYdi Bdg hSde cKjQkG s
(3BNQgG (B:s
(3ef RYe Cf eff Gddg TF eNdhb ChHGjf efg ,agh cGaQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B101 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda (B: ( (3eYGQVI HCUdgG (B)s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs